2020
DOI: 10.1017/s026646232000032x
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement on cancer drug decisions in Europe

Abstract: ObjectivesDespite the efforts of the European Union (EU) to promote voluntary cooperation among Health Technology Assessment (HTA) agencies, different reimbursement decisions for the same drug are made across European countries. The aim of this paper is to compare the agreement of cancer drug reimbursement decisions using inter-rater reliability measures.MethodsThis study is based on primary data on 161 cancer drug reimbursement decisions from nine European countries from 2002 to 2014. To achieve our goal, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…In our study, there was disagreement between SMC and NICE on recommendation or non-recommendation for a minority of technologies (12.6%). This is consistent with previous work that has shown a high degree of agreement between SMC and NICE for cancer therapies compared to other European countries [ 18 , 19 ]. We found that NICE published faster guidance for solid organ therapies but not haematological malignancy therapies than SMC, although the reasons for this are unclear.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there was disagreement between SMC and NICE on recommendation or non-recommendation for a minority of technologies (12.6%). This is consistent with previous work that has shown a high degree of agreement between SMC and NICE for cancer therapies compared to other European countries [ 18 , 19 ]. We found that NICE published faster guidance for solid organ therapies but not haematological malignancy therapies than SMC, although the reasons for this are unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are also in line with those of another article ( 55 ), which compares the agreement of cancer drug reimbursement decisions in nine European countries. Although there is no comparison between France and Italy (Italy is not among the selected countries), this study reported a medium agreement among decisions adopted from 2002 to 2014 by Belgium, Germany, France, Spain, Sweden, Portugal, Poland, England, and Scotland.…”
Section: Discussionsupporting
confidence: 92%
“…Although there is no comparison between France and Italy (Italy is not among the selected countries), this study reported a medium agreement among decisions adopted from 2002 to 2014 by Belgium, Germany, France, Spain, Sweden, Portugal, Poland, England, and Scotland. The adopted methodology is similar, being based on the Cohen's kappa ( 55 ). In addition, our analysis investigated partial agreement, considered a more recent timeframe (July 2017–September 2021), and is not limited to cancer drugs.…”
Section: Discussionmentioning
confidence: 99%